If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + -101 = 7 Reorder the terms: -101 + 6p = 7 Solving -101 + 6p = 7 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '101' to each side of the equation. -101 + 101 + 6p = 7 + 101 Combine like terms: -101 + 101 = 0 0 + 6p = 7 + 101 6p = 7 + 101 Combine like terms: 7 + 101 = 108 6p = 108 Divide each side by '6'. p = 18 Simplifying p = 18
| 4n-40=7(-2n+4) | | 8x-3=15.2 | | s^2-7s=0 | | 49c^2-16=0 | | -6n-2=-2n+4(1-3n) | | -10x-11=-131 | | (x+4)=(x+3) | | -2(3n+8)=-12 | | 5x+20=(x-2)+21 | | -12p-4(2-5p)=5(p-3)-2 | | 3x-3=(x-2)+7 | | 8y-4x=32 | | 6x^2+19x-69=0 | | .005(x+2)=.006x+.006 | | 5y-4x=32 | | x^2=5(x-100) | | .25x+.05(14-x)=.10(-9) | | 7x-4x=x+6 | | 2x+8=98 | | 36-3x=4+x | | 12x+3=2(3x+1)-x+9 | | -2(z-4)-(3z-2)=-2-(6z-2) | | 36-3x=4x | | -x+3+9x=-3+2x+12 | | 6x^2+13x-26=0 | | 28(3x-4)+28(x+3)=28*8 | | 7x+3=19+3x | | 2x^2+3x-90=0 | | x+9y=2 | | 5x-7x=16 | | 7+9(x-2)=6-3(x-7) | | 4x+9x=52 |